A review of human biomonitoring in selected Southeast Asian countries. (July 2018) - Barnett-Itzhaki, Zohar; Esteban López, Marta; Puttaswamy, Naveen; Berman, Tamar
Abstract: Rapid development and industrialization in Southeast (SE) Asia has led to environmental pollution, potentially exposing the general population to environmental contaminants. Human biomonitoring (HBM), measurement of chemical and/or their metabolites in human tissues and fluids, is an important tool for assessing cumulative exposure to complex mixtures of chemicals and for monitoring chemical exposures in the general population. While there are national HBM programs in several developed countries, there are no such national programs in most of the SE Asian countries. However, in recent years there has been progress in the field of HBM in many of the SE Asian countries. In this review, we present recent HBM studies in five selected SE Asian countries: Bangladesh, Indonesia, Malaysia, Myanmar and Thailand. While there is extensive HBM research in several SE Asian countries, such as Thailand, in other countries HBM studies are limited and focus on traditional environmental pollutants (such as lead, arsenic and mercury). Further development of this field in SE Asia would be benefited by establishment of laboratory capacity, improving quality control and assurance, collaboration with international experts and consortiums, and sharing of protocols and training both for pre-analytical and analytical phases. This review highlights the impressive progress in HBM research in selected SE Asian countries and provides recommendations for development of this field. Highlights: We surveyed recent HBM studies in five selected SE Asian countries. There is much potential for improving and harmonizing HBM research in SE Asia. We recommend improving quality assurance and control in HBM research in SE Asia. Other recommendations address improved collaboration with international experts.